Taxonomy and distribution of the genus Eurydice Leach, 1815 (Crustacea, Isopoda, Cirolanidae) from the Arabian region, including three new species - Jones, David Alan; Nithyanandan, Manickam (Zootaxa, 2012)
Three new subtidal species of Eurydice are described, i.e. Eurydice tridentata sp. nov. and Eurydice marisrubri sp. nov.from the Red Sea, and Eurydice marzouqui sp. nov. from the Arabian/Persian Gulf. These species can be separated fromall other Eurydice in the Arabian region by the absence of robust setae on the posterior margin of the pleotelson. E. maris-rubri has a truncate posterior margin bearing 5 apical teeth, E. marzouqui has a rounded pleotelson posterior margin with6 apical teeth and in E. tridentata the posterior margin is truncate, bearing 7 apical teeth, the central 3 prominent. Addi-tional information is provided for two previously described species: E. peraticis Jones, 1974 and E. arabica Jones, 1974.Previous records of E. inermis are attributed to E. tridentata and E. inermis is excluded from the region. A key is providedto separate all the Eurydice species likely to be found in the Arabian region. The distribution of all the Arabian Eurydice is described, and morphology is discussed in relation to habitat.